Kesehatan Mental Dan Implikasinya Dalam Pendidikan Agama Islam Perspektif Pemikiran Zakiah Daradjat - Nadia Ayu Putri; Burhanuddin Ridlwan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Mental health is a very impottant dimension of life, because with mental health life will run smoothly and naturally. Mental health can in general be defined as a normal mental condition and have the motivation to live both professionally and in his or her environment. While islamic education is an institution used as a medium to instill islamic values, it remains in its application and remains a problem for mental health especially in Indonesia. As for the focus of this study is: 1) mental health according to zakiah daradjat. 2) islamic religious education according to zakiah daradjat. 3) mental health implications in islamic religious education according to zakiah daradjat.